STUDENTS’ PERCEPTION ON ENGLISH E-LEARNING DURING COVID-19 PANDEMIC - Nur Anisa Ikhwaty; Muhammad Astrianto Setiadi; Nur Qalbi (Indonesian Journal of Psycholinguistics, 2022)
The Purpose of this study is to find out how students’ perceptions of English E-Learning are reflected in their educational experiences. In other words, researchers are trying to find out whether students are still learning effectively or not using the E-Learning system during the covid-19 outbreak. The method used is descriptive qualitative method. This study was followed by 2 classes in class Seventh student junior high school 1 Bontonompo with a total of 20 students using observation and interview research instruments. Based on the results, the perception on students does not like learning using E-Learning, students prefer to learn face to face directly in class (offline) because students have various difficulties including students who do not understand how to use E-Learning, the limitations of the internet network and the ability to learn English is less improved compared to face-to-face learning in class.